Associations of adverse childhood experiences and suicidal behaviors in adulthood in a U.S. nationally representative sample. (2nd September 2018) - Thompson, Martie P.; Kingree, J. B.; Lamis, Dorian
Abstract: Background: Suicide is a leading cause of death among adolescents and young adults. The current study extends the research linking adverse childhood experiences (ACEs) to suicidal behaviors by testing these associations using a nationally representative sample, assessing for suicide ideation and attempts in adulthood, controlling for established risk factors for suicidality, and measuring a broad array of ACEs. Methods: The sample included 9, 421 participants from the National Longitudinal Study of Adolescent Health who participated in four waves of assessments spanning 13 years. We examined longitudinal associations between eight different ACEs (physical, sexual, and emotional abuse, neglect, parental death, incarceration, alcoholism, and family suicidality) with suicidal ideation and suicide attempts in adulthood, while controlling for depression, problem alcohol use, drug use, delinquency, impulsivity, gender, race, age, and urbanicity. We also tested for cumulative associations of ACEs with suicide ideation and attempts. Results: Logistic regression analyses indicated that physical, sexual, and emotional abuse, parental incarceration, and family history of suicidality each increased the risk by 1.4 to 2.7 times for suicidal ideation and suicide attempts in adulthood. The accumulation of ACEs increased the odds of suicide ideation and attempts. Compared with those with no ACEs, the odds of seriously considering suicide or attempting suicide in adulthood increased more than threefold among those with three or more ACEs. Conclusions: Intervention strategies need to prevent ACEs from occurring and, if they do occur, should take into account the impact of cumulative ACEs on suicide risk. Future research should focus on identifying mediating mechanisms for the ACEs‐suicidality association using longitudinal research designs and determine which ACEs are most important to include in a cumulative ACE measure.